2002
DOI: 10.1614/0043-1745(2002)050[0658:tioshg]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecene inhibitors of Striga hermonthica germination produced by Fusarium solani

Abstract: Metabolites of the fungus Fusarium solani (Sud 96) inhibited Striga hermonthica germination induced by the germination stimulant GR24. The active principles were identified as trichothecenes acuminatin, neosolaniol, 8-acetylneosolaniol, and tetraacetoxy T-2 tetraol (neosolaniol diacetate) on the basis of their chromatographic behavior and nuclear magnetic resonance and mass spectra. Inhibitory activity of the four trichothecenes against Striga germination increased with acetylation of the hydroxyl moieties. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…The inability to produce these toxins by the isolates of F. solani was consistant in all types of culture-media used including the YES-medium which is used by some workers for the production of trichothecenes in particular and some other Fusarium toxins (Krikštaponis et al, 2001;Cvetnić et al, 2005). These findings are in contrast to those of Sugimoto et al (2002) who isolated trichothecenes acuminatin, neosolaniol, 8-acetylneosolaniol, and tetraacetoxy T-2 tetrol (neosolaniol diacetate) from F. solani (SUD96), isolated from infected Striga plants in the Sudan. Such differences in mycotoxin production between different strains of the same species especially when collected from different locations are, however, expected (ApSimon et al, 1990).…”
Section: Discussioncontrasting
confidence: 99%
“…The inability to produce these toxins by the isolates of F. solani was consistant in all types of culture-media used including the YES-medium which is used by some workers for the production of trichothecenes in particular and some other Fusarium toxins (Krikštaponis et al, 2001;Cvetnić et al, 2005). These findings are in contrast to those of Sugimoto et al (2002) who isolated trichothecenes acuminatin, neosolaniol, 8-acetylneosolaniol, and tetraacetoxy T-2 tetrol (neosolaniol diacetate) from F. solani (SUD96), isolated from infected Striga plants in the Sudan. Such differences in mycotoxin production between different strains of the same species especially when collected from different locations are, however, expected (ApSimon et al, 1990).…”
Section: Discussioncontrasting
confidence: 99%
“…However, trichothecenes have not been reported from Neocosmospora or “ F. solani ” except from two isolates misidentified as “ F. solani” ( Ueno et al. 1972 , Sugimoto et al. 2002 ) ( Supplementary Table S2 )…”
Section: Secondary Metabolites Of Fusarioid Generamentioning
confidence: 99%
“…The indirect effect of Fusarium could be through reduction of Striga infestation. In addition the fungus may directly stimulate plant growth (Sugimoto et al, 2002). The present data demonstrated that the application of F. oxysporum was able to reduce the number of Striga plants by 92.52% by attacking the parasite at its different growth stages before emergence as well as before flowering.…”
Section: Discussionmentioning
confidence: 99%